2008
DOI: 10.1088/0004-6256/136/6/2720
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Centers and Noncircular Motions in Things Galaxies: Implications for Dark Matter Halos

Abstract: We present harmonic decompositions of the velocity fields of 19 galaxies from THINGS (The H I Nearby Galaxy Survey) which quantify the magnitude of the non-circular motions in these galaxies and yield observational estimates of the elongations of the dark matter halo potentials. Additionally, we present accurate dynamical center positions for these galaxies. We show that the positions of the kinematic and photometric centers of the large majority of the galaxies in our sample are in good agreement. The median … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
148
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(171 citation statements)
references
References 45 publications
21
148
2
Order By: Relevance
“…They find that that the ellipticity of the potential in the plane of the disk is most likely between 0 and ∼0.06. This is in good agreement with what Trachternach et al (2008) found observationally for a sample of 18 dwarf and spiral galaxies from the THINGS survey de Blok et al 2008), but in disagreement with results from CDM simulations which predict more elongated potentials (e.g., Frenk et al 1988;Hayashi & Navarro 2006). The smaller scatter in the observed BTF relation (e.g., McGaugh 2005), means that it can be used to put similar constraints on lower mass galaxies as well.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…They find that that the ellipticity of the potential in the plane of the disk is most likely between 0 and ∼0.06. This is in good agreement with what Trachternach et al (2008) found observationally for a sample of 18 dwarf and spiral galaxies from the THINGS survey de Blok et al 2008), but in disagreement with results from CDM simulations which predict more elongated potentials (e.g., Frenk et al 1988;Hayashi & Navarro 2006). The smaller scatter in the observed BTF relation (e.g., McGaugh 2005), means that it can be used to put similar constraints on lower mass galaxies as well.…”
Section: Introductionsupporting
confidence: 80%
“…Frenk et al 1988;Hayashi & Navarro 2006). Trachternach et al (2008) also find that the elongation does not increase towards the center of the galaxies. The tightly correlated BTF relation presented in this paper constrains the ellipticity of galaxy potentials using a different method, but reaches similar results.…”
Section: The Scatter Of the Btfmentioning
confidence: 74%
“…We just briefly note that in NGC 7793 the value of the inclination angle fitted by de Blok et al (2008) is low and presents large variations in adjacent radii, which results in a poorly constrained rotation curve. In NGC 2976 the amplitude of the non-circular motions (Trachternach et al 2008) is correlated with the amplitude of the fit residuals.…”
Section: Distancesmentioning
confidence: 97%
“…The IB(s)m galaxy NGC 2366 forms part of "The H i Nearby Galaxy Survey" (THINGS, Walter et al 2008). Its peculiar kinematics were the subject of several recent publications Oh et al 2008;Trachternach et al 2008;van Eymeren et al 2009a, hereafter dB08, Oh08, CT08, and vE09a). The SB(s)m galaxy NGC 4861 was studied by Wilcots et al (1996) and Thuan et al (2004).…”
Section: Observations and Data Reductionmentioning
confidence: 99%